Observation of snow drift flux at Mizuho Station, East Antarctica, 1982 - Takahashi, Shuhei; Ohmae, Hirokazu; Ishikawa, Masao; Katsushima, Takayoshi; Nishio, Fumihiko (1984)
P(論文) Continuous observation of snow drift flux was carried out at Mizuho Station (70°42′S, 44°20′E, 2230m above sea level), East Antarctica, in 1982. Snow drift flux at 1m height was well correlated with wind velocity. The correlation coefficient on a logarithmic plot was between 0.8 and 0.9. The drift flux was proportional to about the 8 power of wind velocity through the year. The power decreased above -20℃. The drift flux increased when precipitation was observed. From the variation of drift flux, precipitation intensity can be estimated. departmental bulletin paper